2007
DOI: 10.2164/jandrol.106.000968
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Resveratrol‐Induced Apoptosis and Cell Cycle Arrest in Prostate Cancer—Derived Cell Lines

Abstract: Resveratrol is a polyphenol found at high concentrations in grapes and red wine with reported anticarcinogenic effects. We studied the molecular mechanism of resveratrol-induced apoptosis and proliferation arrest in prostate derived cells PZ-HPV-7 (nontumorigenic line), LNCaP (androgen-sensitive cancer line), and PC-3 (androgen-insensitive cancer line). Apoptosis and cell cycle distribution were evaluated by flow cytometry and proliferation by MTT assay and direct cell counting. Caspases, bax, bcl-2, cyclins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 62 publications
10
108
0
Order By: Relevance
“…This different potency of RES in prostate tumour cells could be related to downregulation of the expression and function of the AR in androgen-responsive LNCaP cells (Mitchell et al, 1999). Our data also support this different sensitivity of prostate tumour cells to RES, as the higher degree of cell death found in LNCaP with respect to PC-3 (Benitez et al, 2007) appears to correlate with a higher inhibition of PI3K activity in the former. Non-nuclear functions have been described for steroid hormone receptors that emphasise their relevance in signalling pathways controlling proliferation and survival.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This different potency of RES in prostate tumour cells could be related to downregulation of the expression and function of the AR in androgen-responsive LNCaP cells (Mitchell et al, 1999). Our data also support this different sensitivity of prostate tumour cells to RES, as the higher degree of cell death found in LNCaP with respect to PC-3 (Benitez et al, 2007) appears to correlate with a higher inhibition of PI3K activity in the former. Non-nuclear functions have been described for steroid hormone receptors that emphasise their relevance in signalling pathways controlling proliferation and survival.…”
Section: Discussionsupporting
confidence: 83%
“…However, RES inhibited AR and ERa expression in LNCaP and PC-3 cells, respectively. The antiproliferative activity of RES in these cell lines (Benitez et al, 2007), if mediated through PI3K, would most probably produce a specific inhibition of the steroid receptor-associated PI3K (owing to the anti-oestrogenic potential of this molecule) than a global downregulation of cellular PI3K activity. Regardless the decrease in p85 expression, coimmunoprecipitation experiments revealed that none of the concentrations of RES used compromised AR-or ERa interaction with p85 in LNCaP or PC-3, indicating that inhibition of the steroid-receptor-dependent PI3K activity by RES was not due to changes in AR, ERa or p85 levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that grape seed extract and resveratrol at concentrations of 1 to 100 µM have varying degrees of cytotoxic and proapoptotic activity in several cancer cell lines (15). Other researchers showed that resveratrol may decrease the proliferation of tumor cells by inducing apoptosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%